Mechanical Behavior of Parallel Pipelines Under Foundation Pit Excavation - HAN, Chuanjun; MA, Jun; XIE, Rui; ZHANG, Jie (Engineering Transactions, 2018)
In order to study the effect of foundation pit excavation on mechanics of parallel pipeline, a pipeline-soil interaction model was established based on the finite element principle. The deformation of the pipeline by the foundation pit excavation were analyzed. Effect regulations of parallel distance, pipeline parameters and foundation pit parameters on the deformation of the pipeline were studied. The results show that there are two maximum stress areas in pipeline under the action of excavation. The upper and lower surfaces of the pipeline also appear the large stress area. The pipeline has horizontal and vertical displacements. With the increasing of the parallel distance, the deformation of the nearest pipeline increases, but the deformation of the farthest pipeline decreases. With the increasing of the radius-thickness ratio and distance between the foundation pit and the nearest pipeline, the deformation of the pipeline decreases. With the decreasing of the foundation pit width, the deformation of the pipeline decreases. Effect of the foundation pit’s length on the pipeline is not obvious.